Roles of Awareness and Knowledge in Determining People’s Perception Towards Takaful: Evidence from Southwestern Afghanistan - Abdullah, Ziarmal; Shams, Shamsullah; Ashurov, Sharofiddin (El-Barka Journal of Islamic Economics and Business, 2023)
The main purpose of this study is to investigate the impact of awareness and knowledge in determining people’s perceptions towards takaful services in Afghanistan's southwestern zone, with a particular focus on the provinces of Kandahar, Helmand, and Zabul. This study aims to shed light on the elements impacting people's perceptions of takaful by assessing their awareness and understanding levels of takaful in the specified geographic and socioeconomic environment. To achieve the study objective, an expert research methodology is adopted. It includes survey-based inquiries conducted using a carefully chosen heterogeneous purposive sampling (HPS) technique. The data collected is subjected to rigorous analysis, including reliability testing, multiple regression, and Pearson correlation analysis. The robust analysis is facilitated by the utilization of SPSS version 26:00 software. The results state that the role of awareness and knowledge is established as statistically significant and has a positive impact on shaping individuals' perceptions towards takaful services within the southwestern zone of Afghanistan. To enhance the breadth of future research, it is recommended that similar investigations be extended to other provinces, fostering a more comprehensive understanding. As an avenue for future exploration, subsequent studies could delve into additional determinants of individuals' perceptions that may have been unaddressed in this research. The insights garnered from this study possess significant implications for policymakers seeking to facilitate the establishment of the takaful industry, with a particular emphasis on aligning regulatory measures with Sharia law and focusing on the salient determinants that influence individuals' perceptions.